Vtc5 Is Localized to the Vacuole Membrane by the Conserved AP-3 Complex to Regulate Polyphosphate Synthesis in Budding Yeast - Amanda Bentley-DeSousa (American Society for Microbiology, 2021)
Long polymers of inorganic phosphates called polyphosphates are ubiquitous across biological kingdoms. From bacteria to humans, they have diverse functions related to protein homeostasis, energy metabolism, and cell signaling.